Analysis of Science Process Skills, Perceptions, and Learning Outcomes in the Implementation of Ethnoscience-Based Student Worksheets on the Nature of Physics and Scientific Methods - Alfons Bunga Naen; Theresia Wariani; Vinsensia H. B. Hayon; Maria Ursula Jawa Mukin; Maria Lia Felizarda Freitas; Hironimus Tangi; Yanti Rosinda Tinenti; Ilidio Ximenes Moreira (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to examine the effectiveness of Ethnoscience-Based Student Worksheets (EbSWs) on the subject matter of the nature of physics and the scientific method. The research subjects were 10th-grade students at SMAK Sint Carolus Penfui. This is a descriptive quantitative study using tests to measure cognitive learning outcomes and Science Process Skills (SPS), while questionnaires were used to measure student perceptions (attitudes, skills, and knowledge). The results showed that EbSW were effective in optimizing students' SPS, with an overall average score of 83.90 (very skilled) and a high consistency of results (standard deviation/SD = 3.61). Student perceptions were very positive, with knowledge (average 83.7) and attitude (average 82.1) aspects categorized as very good. SPS perception results (average 77.9) were categorized as good and showed an increase in higher-level cognitive skills. Cognitive learning outcomes showed a level of mastery (mean = 80.67) with a cognitive SD of 19.07, indicating a gap in mastery of the material among students, especially in higher-order thinking skills (HOTS). Overall, EbSW are effective for understanding basic concepts and developing SPS evenly but need to be improved to address varying levels of HOTS mastery.